#### Answer

The sequence is arithmetic.
Recursive formula : A(n) = A(n - 1) + 0.6 ; A(1) = 0.3
Explicit formula : A(n) = 0.3 + (n - 1)(0.6)

#### Work Step by Step

The sequence is arithmetic because there is a common difference between all the terms which is 0.6
Explicit formula- For this formula we need to find the d value and A(1) and we can find the d value by subtracting the second term from the first.
D = 0.9-0.3
D= 0.6
A(1) = 0.3 ; We can now form the equation A(n) = 0.3 + A(n - 1)(0.6)
Recursive- For this formula, we need the common difference and A(1) and since the common difference is the same as the d value in the explicit formula, we can use that.
Common difference = 0.6
A(1) = 0.3; We can now form the equation A(n) = A(n - 1) +0.6 ; A(1) = 0.3